Stimulating Early Children’s Knowledge about Shape Using the Geometry Board - Madang, Septina; Ariesti, Irvinia; Apriani, Maria; Lestari, Sesilia Dea; Masrifah, Alviyani; Kezia, Kezia; Rozie, Fachrul (GENIUS: Indonesian Journal of Early Childhood Education, 2022)
This study aims to describe the use of learning media products in the form of geometric boards to develop children's cognitive abilities aged 4-5 years. Using the geometric board as media, children can easily recognize geometric shapes such as triangles, rectangles, circles, semicircles, rectangles, and parallelograms. This type of research uses an approach with a descriptive analysis model. The data analysis stage uses the Miles and Huberman model, including compaction, data presentation, and concluding. In this study, the the researcher chose to conduct research in kindergarten. The informants observed were children aged between 4 to 5 years who were in early childhood education and their parents. To check the validity of the data, using the triangulation technique. The results of the study found that using the geometry board was very helpful for parents in introducing geometry to their children. The media is made of simple materials that are easy to find, so it is not difficult to make. Children also become more interested in learning and are willing to learn various shapes of objects. Abstrak Penelitian ini bertujuan untuk mendeskripsikan tentang pemanfaatan produk media pembelajaran berupa papan geometri untuk mengembangkan kemampuan kognitif anak usia 4-5 tahun. Manfaat dari penggunaan media papan geometri ini agar anak dapat mengenal bentuk-bentuk geometri seperti bentuk segitiga, segi empat, lingkaran, setengah lingkaran, persegi panjang, dan jajaran genjang. Jenis penelitian ini menggunakan pendekatan kualitatif dengan model analisis deskriptif. Tahap analisis data menggunakan model Miles dan Huberman yang meliputi pemadatan data, penyajian data, dan penarikan kesimpulan. dalam penelitian ini peneliti memilih untuk melakukan penelitian di taman kanak-kanak. Informan yang diamati adalah anak-anak berusia antara 4 sampai 5 tahun yang berada dalam masa pendidikan anak usia dini serta orang tuanya. Untuk mengecek keabsahan data, peneliti menggunakan teknik triangulasi. Hasil penelitian menemukan bahwa penggunaan papan geometri sangat membantu orang tua dalam mengenalkan geometri kepada anak-anak. Media terbuat dari bahan-bahan sederhana yang mudah ditemukan sehingga tidak sulit pembuatannya.anak-anak juga menjadi lebih tertarik belajar dan memiliki kemauan untuk mempelajari ragam bentuk benda.